La valeur du corps saint d’après les Vitae des mulieres religiosas des Pays-Bas méridionaux du xiiie siècle - Anne-Laure Méril-Bellini delle Stelle (Les Cahiers de Framespa, 2014)
Far from the usual clichés about Christianity in the medieval West, hagiographic literature attests to the value of the body, including that of women, at least if they were holy. Indeed, hagiographers who write the Vitae of several mulieres religiosae from thirteenth-century Southern Low Countries, consider that the body has value since it is a key of the imitatio Christi. It ensures an exchange between the Lord and the devotee, but also with a third beneficiary to whom the mystical willingly gives the divine advantages she has received. This valuation, which from a feminist perspective has long been interpreted as a denial of the spiritual qualities of women, must be examined anew, because Vitae dedicated to contemporary viri Dei sometimes introduced the same process of development of holiness by the spiritualized body. This is the case with a Cistercian lay brother such as Arnulf of Villers, while the choir monks or preacher do not share this spiritual model, which shifts the issue of the price assessement of the holy body from gender to religious status and thereby allows to consider in a new light medieval social hierarchies set by the Church as well as the role played by the body.